Analisis spektrum resonansi spin electron kristal tak isotrop bersimetri aksial (serbuk cu so4 5h20) dengan spektrum bentuk Lorentz dan Gauss - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1988)
Electron spin resonance using Bruker's ER 200 tt spectrometer has been investigated at room temperature with the axially symmetrical Cu SO4 5H20 crystal powders as samples. The resonance spectra for various sample masses were analyzed using the Lorenzian and Gaussian asymmetric parameter fitting on a rainbow 100 microcomputer. The resulting paramagnetic splitting factors, gl = 2.22 ± 0,01 and gli = 2.09 ± 0,02 due to the Exchange and the Dipole Dipole interaction were obtained. The Exchange interaction energy, which caused the narrowing of spectra peak, was computed to be J = (1.9 ± 0,2) 117'55 joule while the dipole-dipole interaction, which caused spectra broadening, contributed a peak width L131/2 = 0.0055 tesla by neglecting the effects of fine/hyperfine splitting and temperature fluctuation. The broadening of spectra due to the presence of the lical field appearing in the dipole-dipole interaction of the sample spin system, contributed to the line spectra more modified GaTicsian peak instead of a Lorenzian shape The modification of the Gaussian line were due to the presence of exchange interaction